2016
DOI: 10.1074/jbc.m116.723650
|View full text |Cite
|
Sign up to set email alerts
|

Mga2 Transcription Factor Regulates an Oxygen-responsive Lipid Homeostasis Pathway in Fission Yeast

Abstract: Eukaryotic lipid synthesis is oxygen-dependent with cholesterol synthesis requiring 11 oxygen molecules and fatty acid desaturation requiring 1 oxygen molecule per double bond. Accordingly, organisms evaluate oxygen availability to control lipid homeostasis. The sterol regulatory element-binding protein (SREBP) transcription factors regulate lipid homeostasis. In mammals, SREBP-2 controls cholesterol biosynthesis, whereas SREBP-1 controls triacylglycerol and glycerophospholipid biosynthesis. In the fission yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 68 publications
6
57
0
Order By: Relevance
“…In this light, the ER-membrane serves as 'memory device' to integrate a long-term signal for oxygen availability, which is encoded by the lipid composition (Covino et al, 2016;Ernst et al, 2016). This elegant mechanism of signal integration is apparently conserved among fungi, as the homolog of Mga2 in S. pombe was recently identified as oxygen-responsive modulator of lipid homeostasis (Burr et al, 2016).…”
Section: Mga2 and Spt23 As Key Regulators Of Membrane Fluiditymentioning
confidence: 99%
See 1 more Smart Citation
“…In this light, the ER-membrane serves as 'memory device' to integrate a long-term signal for oxygen availability, which is encoded by the lipid composition (Covino et al, 2016;Ernst et al, 2016). This elegant mechanism of signal integration is apparently conserved among fungi, as the homolog of Mga2 in S. pombe was recently identified as oxygen-responsive modulator of lipid homeostasis (Burr et al, 2016).…”
Section: Mga2 and Spt23 As Key Regulators Of Membrane Fluiditymentioning
confidence: 99%
“…Loss of both transcription factors is lethal within a few cell divisions unless UFAs are present in the growth medium, while single deletions are viable even in the absence of exogenous UFAs (Zhang et al, 1997). Homologs of Mga2 and Spt23 have been characterized in the fission yeast Schizosaccharomyces pombe and the pathogenic fungus Candida albicans (Oh and Martin, 2006;Burr et al, 2016). The remarkable sequence conservation of Mga2 and Spt23 among fungi including multiple pathogenic strains, and the absence of an obvious homolog in mammals makes these proteins intriguing drug targets for anti-fungal therapy.…”
Section: Mga2 and Spt23 As Key Regulators Of Membrane Fluiditymentioning
confidence: 99%
“…Recently, multiple Cbf11 target genes, including cut6, vht1 and bio2, were shown to be regulated by Mga2, a transcription factor (analogous to mammalian SREBP-1) controlling oxygen-responsive lipid homeostasis in S. pombe. 49 However, it is not yet clear whether or how Cbf11 and Mga2 cooperate to regulate lipid metabolism and/or cellcycle progression. Intriguingly, it has recently been reported that mammalian cells remodel their membrane lipid composition during the cell cycle, and these periodic changes are important for proper cell-cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…The Mga2 transcription factor is important for lipid homeostasis and shares a number of target genes with Cbf11. Also, the degrees of activatory contribution of Mga2 and Cbf11 seem to be similar for many of their shared target genes (Burr et al, ; Převorovský et al, ). Strikingly, no cut phenotype has been reported for the mga2∆ mutant.…”
Section: Cut Mutants Linked To Fatty Acid (Fa) Anabolismmentioning
confidence: 99%